1998
DOI: 10.1002/jor.1100160206
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cooling on cutaneous microvascular adrenoceptors in vivo in the rabbit ear

Abstract: Previous studies have suggested that moderate cooling increases the responsiveness of vascular alpha2-adrenoceptors. However, limited information is available documenting the influence of temperature changes on adrenoceptor responses in the microvasculature of thermoregulatory organs (e.g., the human digit and the rabbit ear) subjected to a wide range of temperatures. In the present study, the effect of local cooling (24 degrees C) on cutaneous microvascular adrenoceptors in the ear was observed in vivo in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
4
2
0
Order By: Relevance
“…This is in agreement with previous reports on this and other vascular smooth muscle preparations in the literature . Several studies have shown that cooling has a variable effect on vascular smooth muscle preparations ranging from relaxation in deep vessels to vasoconstriction in cutaneous arteries . Our present results showed that cooling significantly reduced PE‐induced contractions of aorta segments without PVAT.…”
Section: Discussionsupporting
confidence: 94%
“…This is in agreement with previous reports on this and other vascular smooth muscle preparations in the literature . Several studies have shown that cooling has a variable effect on vascular smooth muscle preparations ranging from relaxation in deep vessels to vasoconstriction in cutaneous arteries . Our present results showed that cooling significantly reduced PE‐induced contractions of aorta segments without PVAT.…”
Section: Discussionsupporting
confidence: 94%
“…Our results evaluated in vivo by RCM are in agreement with previous studies on temperature induced alterations in human skin microcirculation [11][12][13][14]. Recently, Ciplak et al studied the vasodilatory response of skin microcirculation to local heating using laser Doppler imaging [12].…”
Section: Discussionsupporting
confidence: 94%
“…Based on RCM observations, we are not only able to confirm, but also to quantify this fact in vivo on a histomorphological level, as we assessed cold stress-dependant significant decrease of the capillary size. Moreover, in accordance with previous studies [14] we observed a concomitant decrease of single blood cell flow, induced by local cold stress. In this study, the area of interest was covered prior to contact with water in order not to confound histomorphological data.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus temperature appears to regulate cellular distribution and second messenger coupling of α 2C -AR. Clinical studies in Raynaud's patients have also documented a significant role for α 2 -ARs in the exaggerated cold-induced vasoconstriction typical of this syndrome [40,43,44], although there are other reports that α 2 -AR blockade has little or no effect on cold-induced vasoconstriction [45][46][47]. In addition, the α 2C -ARs appear to contribute to cerebral blood flow by regulating tone in the carotid artery [48,49], and recent studies suggest subtype selective activation of these receptors causes vasoconstriction which may be a beneficial therapy for migraine [38,49].…”
Section: Physiological Actions In the Peripheral Circulationmentioning
confidence: 99%